2018
DOI: 10.1353/csd.2018.0042
|View full text |Cite
|
Sign up to set email alerts
|

"Black Elephant in the Room": Black Students Contextualizing Campus Racial Climate Within US Racial Climate

Abstract: The systemic racism in U.S. society being resisted through larger movements such as Black Lives Matter is also reflected and reproduced in U.S. higher education. This qualitative study examines how Black students contextualize their campus racial climate within broader race issues, tensions, and movements occurring across the nation. Findings reveal four themes: (1) Perceptions of Blackness on campus; (2) Campus racial climate mirroring societal racial climate; (3) Experiencing and engaging in movements on cam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
79
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(97 citation statements)
references
References 33 publications
2
79
0
Order By: Relevance
“…While our discussion focused on a framework involving the compositional, interactional, and organizational components of diversity, we also believe future research should consider two other related lines of research: students' perceptions of climate toward racial diversity and the external environment in which schools are located. Both of these have more recently emerged within the higher education framework (Cuellar & Johnson‐Ahorlu, 2020; Hurtado et al., 2012; Mwangi et al., 2018). However, these fields are also not new to the K12 literature.…”
Section: Discussionmentioning
confidence: 99%
“…While our discussion focused on a framework involving the compositional, interactional, and organizational components of diversity, we also believe future research should consider two other related lines of research: students' perceptions of climate toward racial diversity and the external environment in which schools are located. Both of these have more recently emerged within the higher education framework (Cuellar & Johnson‐Ahorlu, 2020; Hurtado et al., 2012; Mwangi et al., 2018). However, these fields are also not new to the K12 literature.…”
Section: Discussionmentioning
confidence: 99%
“…These findings extend the literature on student-faculty relationships by linking a specific dimension of student-faculty relationships (i.e., caring faculty) with Black students' perceptions of the campus climate and their academic engagement. Furthermore, the presence of caring faculty at PWIs illustrate one potential pathway for improving Black students' perceptions of the campus climate and improving their engagement on campus (George Mwangi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Racial identity has been defined as one's sense of sharing common heritage with a particular racial group and one's psychological connectedness to this reference group (Cokley & Vandiver, 2012). This aspect of Black students' identity has received significant empirical attention given it is correlated with the academic and psychological adjustment of Black students at PWIs (Chavous et al, 2018;George Mwangi et al, 2018). However, if race is not seen as an important component of the Black learner's overall identity, it may be less likely to have an influence on their academic performance (Thomas et al, 2009).…”
Section: Cultural Variables and Black Students' Academic Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Students of Color may also experience racial discrimination and microaggressions from their peers beyond the campus context. George Mwangi et al (2018) found that Black college students viewed their campus racial climate as an extension of the overall racial climate in the United States. Since students of Color may blur their online and in-person experiences with racialized aggressions, more research is needed to expand how these "campus experiences" influence their mental health.…”
mentioning
confidence: 99%